2017
DOI: 10.1080/14015439.2017.1381148
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of speech production in patients with T1 glottic cancer who underwent laser cordectomy or radiotherapy

Abstract: The differences may have been due to muscular fibrosis after RT. Movements of vocal cords with fibrosis were sluggish, when impulsion developed to pronounce the initial /p/ sound, so the VOT was shortened and the VD was longer after RT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 7 publications
0
8
1
Order By: Relevance
“…Literature revealed various advantages of Laser surgery like it showed little bit of laryngeal edema, decreased morbidity rate, few side effects and a quick procedure but on the other hand, reported some side effects as well, including relapse because of incomplete tumorous tissue to preserve the voice. 11,12 These findings are supported by the current study but contradicting to the studies that consider Laser surgery as a best option for early glottic cancer because of better survival and few complications. 1, 13,14 Radiotherapy is considered as a primary treatment option for early stage glottic cancer because of the preservation of laryngeal anatomy and voice as well.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…Literature revealed various advantages of Laser surgery like it showed little bit of laryngeal edema, decreased morbidity rate, few side effects and a quick procedure but on the other hand, reported some side effects as well, including relapse because of incomplete tumorous tissue to preserve the voice. 11,12 These findings are supported by the current study but contradicting to the studies that consider Laser surgery as a best option for early glottic cancer because of better survival and few complications. 1, 13,14 Radiotherapy is considered as a primary treatment option for early stage glottic cancer because of the preservation of laryngeal anatomy and voice as well.…”
Section: Discussioncontrasting
confidence: 72%
“…2000-3000 cGy. 18,19 Hong et.al compared both treatment modalities and concluded that there was shortened voice onset time and vowel duration after Radiotherapy rather than Laser surgery, might be due to muscular fibrosis leads to sluggish vocal cord movements 11 and this finding was supported by another study, that manifested multidimensional deficits in function of vocal cord for about 2-7 years. 20 On the other hand, the systematic review by Huang et.al reported the advantage of Radiotherapy as an increased maximum phonation time and reduced fundamental frequency.+7 But some of the studies showed no significant difference among the outcomes.…”
Section: Discussionmentioning
confidence: 97%
“…Patients who had undergone RT showed increased MPT and decreased frequency (F0) compared to those with LS. LS generally results in loss of tissue while RT leads to vocal fold fibrosis and muscle fatigue [9]. The objective of the present meta-analysis was to evaluate voice quality of LS and RT based on the grade, roughness, breathiness, asthenia, and strain (GRBAS) scale and acoustic analysis parameters including frequency–perturbation (jitter), measures of amplitude–perturbation (shimmer), and noise to harmonic ratio (NHR).…”
Section: Introductionmentioning
confidence: 99%
“…Treatment for laryngeal neoplasms with laser or surgical excision is the common cause of vocal scar . Radiotherapy has previously been explored as a way to preserve laryngeal structures while treating neoplasms, but tissue fibrosis has still been shown to occur, and there are constraints in repeating radiotherapy . Currently, treatment options for vocal scars produces inconsistent and often unsatisfactory results .…”
Section: Introductionmentioning
confidence: 99%
“…2 Radiotherapy has previously been explored as a way to preserve laryngeal structures while treating neoplasms, but tissue fibrosis has still been shown to occur, and there are constraints in repeating radiotherapy. 3 Currently, treatment options for vocal scars produces inconsistent and often unsatisfactory results. 4 Thus, there is a need for more efficacious management of vocal fold scarring or a treatment modality for laryngeal neoplasms that will not induce symptomatic postsurgical scarring in the first place.…”
Section: Introductionmentioning
confidence: 99%